The original polyethylene microplastics inhibit the growth of sweet potatoes and increase the safety risk of cadmium - Shi, Liang; Chen, Zanming; Hou, Yanan; Li, Jianmin; Shen, Zhenguo; Chen, Yahua (Frontiers in Plant Science, 2023)
Microplastics (MPs) and heavy metal (HM) co-exist in sweet potato fields of China. As the main component of agricultural field mulch and one of the most polluting and harmful heavy metals (HMs), the effects of polyethylene microplastics (PE MPs) and cadmium (Cd) on sweet potato and soil environment are remains unclear. In this study, the results of pot experiments reveal that compared with the control (0%), 5% of weathered PE MPs can significantly increase soil electrical conductivity (EC); both 5% of the original PE MPs and weathered PE MPs can significantly reduce the concentration of Olsen phosphorus (P) and Olsen potassium (K) in soil, inhibit plant growth, but significantly increase Cd accumulation and glutathione (GSH) level in tissues of sweet potatoes, and also induce membrane lipid peroxidation. In addition, compared to 5% weathered PE MPs, 5% original PE MPs significantly reduce soil EC, growth and peroxidase level of sweet potatoes, but significantly increase Cd concentration in leaves and stems. The results of hydroponic experiment show that original PE MPs significantly increase the P, K, and Cd adsorption compared with weathered PE MPs, and Cd increases the original PE MPs accumulation in the root cortex but decrease PE MPs accumulation in shoots.